Internalisasi Karakter Religius Melalui Model Blended Learning dalam Pembelajaran PAI di Masa Pandemi Covid-19 - Fathurrahman Fathurrahman; Anang Fahrur Rozi (Institut Agama Islam Al-Hikmah Tuban, 2022)
Abstract: This research focuses on internalisation of religion character through learning blended model in learning of Islamic education in the pandemic covid 19 era at SMK Muhammadiyah 1 Lamongan. The proses of basic and improvement character of the students is the main topic that must be noticed in the online or offline class. So that, it is important to create internalisation of religion character which is connected with learning proses on Islamic education. Learning blended model can be applied to internalize the religion character. The tipe of blended learning which is improved by SMK Muhammadiyah 1 Lamongan is enriched virtual model using 2 online and 7 offline. This type and proportion are to improve religion character for the students in the pandemic of covid 19 era. The teachers at Islamic education plan some equipment such as lesson plan, learning media, and evaluation system through assesment instrument planned by the teachers. Learning blended model as the proses internalisation of religion character at SMK Muhammadiyah 1 Lamongan has some weakness which becomes the problem, but the support of government policy, school management, teacher cohesiveness in the implementation of MGMP, and the supports of a good infrastructure are the important factors in the success of learning.